Inference of Adaptive methods for Multi-Stage skew-t Simulated Data - Loai M. A. Al-Zou’bi; Amer I. Al-Omari; Ahmad M. Al-Khazalah; Raed A. Alzghool (European Scientific Journal, ESJ, 2017)
Multilevel models can be used to account for clustering in data from multi-stage surveys. In some cases, the intra-cluster correlation may be close to zero, so that it may seem reasonable to ignore clustering and fit a single level model. This article proposes several adaptive strategies for allowing for clustering in regression analysis of multi-stage survey data. The approach is based on testing whether the cluster-level variance component is zero. If this hypothesis is retained, then variance estimates are calculated ignoring clustering; otherwise, clustering is reflected in variance estimation. A simple simulation study is used to evaluate the various procedures.